AND LANDSCAPE-ECOLOGICAL ANALYSIS OF ITS DISTRIBUTION - S. M. Musaeva (Юг России: экология, развитие)
The article is devoted to the study of helminthofauna of the striped lizard in Lankaran natural region. The landscape and ecological analysis of distribution of the helminthofauna is provided. As a result of studies on 99 individuals of striped lizard totally 14 species of helminthes, including 1 trematode species, 1 species of cestode, 3 species of akantocefals and 9 species of nematodes were found.